Flight plan generation for unmanned aerial vehicles - Noonan, Andrea L. (Kansas State University, 2007)
The goal of this research is to develop methods and tools for generating flight plans for an unmanned aerial vehicle (UAV). A method of generating flight plans is needed to describe data collection missions, such as taking aerial photographs. The flight plans are two-dimensional and exist in a plane a fixed distance above the Earth. Since the flight areas are typically small, the Earth's curvature is not accounted for in flight plan generation. Designed to completely cover a specified field area, the plans consist of a series of line and arc segments and are described in a format that is recognized by the Piccolo autopilot used by the Kansas State University Autonomous Vehicle Systems (AVS) Lab. Grids are designed to cover the field area, and turn maneuvers are designed to ensure efficient flight plans. The flight plan generation process is broken into several parts. Once a field area is defined, path lines covering this area are calculated. Optimal turn maneuvers are calculated to smoothly connect the path lines in a continuous flight plan. Two methods of determining path line order are discussed. One method flies the lines in the order that they are arranged spatially; the other method decides line order by calculating the shortest turn maneuver to another path line. After the flight plan is generated, a text file is created in a format that is readable for the autopilot. In order to easily generate flight plans, a graphical user interface (GUI) has been created. This GUI allows a user to easily generate a flight plan without modifying any code. The flight plan generation software is used to build example flight plans for this thesis. These flight plans were flown with an UAV and test results are presented.
Keywords: uav; path planning; Engineering, Mechanical (0548); Remote Sensing (0799)